Vitamin K and women's health: a review - AlBlooshi, Sharifa (Frontiers in Global Women's Health, 2025)
Vitamin K is a fat-soluble vitamin essential in various physiological functions such as blood coagulation, bone metabolism, cardiovascular health, glucose regulation, immune function, neuroprotection, and vascular health. In this narrative review, studies from databases including PubMed, Google Scholar, Scopus, and the institutional database of Zayed University were selected. The role of vitamin K in women's health, with a focus on osteoporosis, postmenopausal health, cardiovascular health, diabetes, cancer, kidney health, brain health, vascular health, and pregnancy were explored. The role of vitamin K in activating vitamin K-dependent proteins is essential for many of its functions. Vitamin K-dependent proteins such as osteocalcin and matrix gla protein are crucial to many physiological processes such as bone mineralization, vascular calcification, and cardiovascular health. It also modulates glucose metabolism by enhancing insulin sensitivity, reducing oxidative stress, and influencing β-cell function. Vitamin K exhibits anti-cancer properties in cancer research, particularly in breast, cervical, and ovarian cancer models. It also plays a role in brain health including cognitive function, neuroinflammation reduction, and neurodegenerative disease prevention. Similarly in kidney diseases, vitamin K has been linked to chronic kidney disease progression and vascular calcification. Vitamin K's role in pregnancy includes its impact on neonatal coagulation and neurodevelopmental outcomes. Despite the promising role of vitamin K, findings are mixed on its role in bone mineral density and fracture prevention, cardiovascular protection, protection against vascular calcification, diabetes prevention, cancer risk, kidney dysfunction, and its role in maternal and child health. These highlight the need for further research, particularly longitudinal and randomized controlled trials, to determine optimal intake, efficacy of supplementation, and long-term health impacts of vitamin K in women.